El interpretar en el camino de la comprensión: hacia una semiohermenéutica desde CH. S. Peirce Y H. G. Gadamer - Agudelo Rendón, Pedro (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
One of the fundamental aspects when approaching comprehension as a method in the question of interpretation. What interpretation is and means is defined by what is in question regarding comprehension. This work presents a semiotic route, following Peirce, and a hermeneutic route, following Gadamer, in order to define the concept of interpretation and demonstrate its vital importance for comprehension as a method. Thus, the concept of sign —interpretation itself in its most definitive aspect. In order to achieve such objective we follow a descriptive and contrastative methodology which describes the notion of interpretation for both authors and presents their points of convergence.